THE EFFECT OF PROBLEM BASED LEARNING MODEL ON IMPROVING MATHEMATICAL CRITICAL THINKING ABILITY AND STUDENT LEARNING INDEPENDENCE IN MAN 1 MEDAN - Siregar, Ahmad Rifai; Hasratuddin, Hasratuddin; Rangkuti, Yulita Molliq; Landong, Ahmad; Siregar, Julya Syahleni; Siregar, Fadhillah Rahma (FKIP Universitas Muhammadiyah Tangerang, 2025)
The objectives of this research were to determine: (1) the effect of the Problem Based Learning learning model is better than the Ordinary Learning Model on improving students' critical mathematical thinking skills; (2) the interaction between learning and students' initial mathematical abilities on improving students' critical mathematical thinking skills; (3) the effect of the Problem Based Learning learning model is better than the Ordinary Learning Model on improving students' learning independence; (4) the interaction between learning and students' initial mathematical abilities on improving students' learning independence. The population in this study consisted of all tenth-grade students at MAN 1 Medan, and the sample comprised 60 students from classes X-9 and X-6, divided into experimental and control groups. The instruments used included a mathematical critical thinking skills test and a learning independence scale. Data were analyzed using two-way ANOVA. Based on the analysis, the following results were obtained: (1) The Problem Based Learning learning model has a better effect than the ordinary learning model in improving students' critical mathematical thinking skills; (2) there is no interaction between learning and students' initial mathematical abilities on improving students' critical mathematical thinking skills; (3) The Problem Based Learning learning model has a better influence than the ordinary learning model in increasing students' learning independence; (4) there is no interaction between learning and students' initial mathematical abilities towards increasing students' learning independence. Based on the results of this study, it is suggested that learning with problem based learning be used as an alternative for teachers to increase students' critical mathematical thinking skills and learning independence.